1971
DOI: 10.1111/j.1365-2141.1971.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Regulation of Granulopoiesis

Abstract: Summary. Tritiated thymidine autoradiography was used to study the control of granulocyte production and release using the irradiated leg shielded mouse as an experimental model. Neutropenia resulted in a shortening of 24–36 hr in the mean transit time through the non‐proliferating granulocyte compartment. There was little difference between neutropenic and control animals in labelling indices of the cells in the proliferative granulocyte compartments, which suggests that the granulocytic hyperplasia observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

1973
1973
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Other workers have provided evidence that ALS destroys or neutralizes the functions of a variety of circulating and fixed tissue cells other than lymphocytes, including other leucocytes, splenic giant cells and even epithelial and connective tissue elements (see Yoffey and Courtice, 1970). The glomerular mesangeitis produced rapidly by the nephrotoxic action of ALS on the kidney (Lindquist et al, 1969) (Puck and Marcus, 1956) and in vivo (Revesz, 1958; van den Brenk and Shlarpington, 1971b), a "leucocyte stimulating factor " in granulopoiesis (Metcalf,1 970) which is also present in serum of irradiated mice (Morley et al, 1971;Rickard et al, 1971a, b), a portal blood factor acting as a hlutmoral agent in liver regeneration (Fisher et al, 1971), a HeLa cell stimulating factor in normal calf serum (Salmon and Hosse, 1971) and polyaminies derived from ornithine in tissues which stimulate normal aand neoplastic growth (Tabor and Tabor, 1964;Bucher and Malt, 1971 (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Other workers have provided evidence that ALS destroys or neutralizes the functions of a variety of circulating and fixed tissue cells other than lymphocytes, including other leucocytes, splenic giant cells and even epithelial and connective tissue elements (see Yoffey and Courtice, 1970). The glomerular mesangeitis produced rapidly by the nephrotoxic action of ALS on the kidney (Lindquist et al, 1969) (Puck and Marcus, 1956) and in vivo (Revesz, 1958; van den Brenk and Shlarpington, 1971b), a "leucocyte stimulating factor " in granulopoiesis (Metcalf,1 970) which is also present in serum of irradiated mice (Morley et al, 1971;Rickard et al, 1971a, b), a portal blood factor acting as a hlutmoral agent in liver regeneration (Fisher et al, 1971), a HeLa cell stimulating factor in normal calf serum (Salmon and Hosse, 1971) and polyaminies derived from ornithine in tissues which stimulate normal aand neoplastic growth (Tabor and Tabor, 1964;Bucher and Malt, 1971 (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Germ-free mice have abnormally low serum CSF levels (Metcalf, Foster and Pollard, 1967a), emphasizing the role of bacterial products in provoking CSF production by the tissues. Furthermore, serum CSF levels in germ-free mice are not elevated by whole-body irradiation, as occurs following irradiation of conventional mice (Morley et al, 1971. It seems possible therefore that the capacity of C-type viruses to induce myeloid leukaemia development may be dependent on a sufficient proliferative pressure being applied by CSF on the virus-altered granulopoietic cells to force the emergence of an abnormal (leukaemic) subpopulation.…”
Section: Preleukaemic Changesmentioning
confidence: 91%
“…Studies of CSF levels in mice and humans during fluctuations in the level of granulopoiesis or monocyte formation, together with observations on the in vivo effects of injected preparations of CSF, suggest that CSF is a humoral regulator of granulopoiesis and monocyte formation (Bradley et al, 1969;Metcalf and Stanley, 1971;Metcalf and Moore, 1971;Morley et al, 1971).…”
mentioning
confidence: 99%
“…Fried et al (1973) reported that this effect was due to modification of the marrow micro-environment, although a possible humoral effect was not ruled out. Morley et al ( 1971) suggested that there was a close relationship between the colony stimulating activity of serum and the level of granulocytopenia in irradiated mice. The results presented here do not support this proposal since higher serum CSF levels were detected in control mice in the absence of granulocytopenia.…”
Section: Discussionmentioning
confidence: 99%